THE CURRENT STATE OF RUSSIAN REGIONAL INTERNET MEDIA (ON THE EXAMPLE OF THE REPUBLIC OF TATARSTAN) - Nagovitsyna, Tatiana A.; Gazizov, Ramis R. (Gênero & Direito, 2019)
The paper concerns the determination of the state of development of the Internet mass media (on the example of the Republic of Tatarstan). It considers the issues of formation and the regional peculiarities of this type of media environment, summarizes the experience of the Internet media of the Republic of Tatarstan. The authors focus special attention on multimedia, as a factor in the development of networked media at the present stage. The specifics of the Internet media has significantly changed the nature of the presentation of materials, the work of journalists, the target audience, as well as the system of functioning of the media in general. The authors analyzed the nature of the influence of multimedia on the features of functioning of regional networked media. In recent years, the Republic of Tatarstan remains among the most reading regions in Russia. As of today in the given region of Russia there is registered 1067 mass-media. In connection with the development of the Internet media, which today determine the leading trends in the functioning of all the mass media, it seems to us necessary to consider the peculiarities of the Internet media of the Republic of Tatarstan.